2010
DOI: 10.1103/physrevb.81.165105
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of turbostratic graphene

Abstract: We explore the rotational degree of freedom between graphene layers via the simple prototype of the graphene twist bilayer, i.e., two layers rotated by some angle $\theta$. It is shown that, due to the weak interaction between graphene layers, many features of this system can be understood by interference conditions between the quantum states of the two layers, mathematically expressed as Diophantine problems. Based on this general analysis we demonstrate that while the Dirac cones from each layer are always e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
309
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(321 citation statements)
references
References 25 publications
10
309
2
Order By: Relevance
“…[77] As the twist angle decreases, the size of the unit cell enlarges [78] and the number of atoms comprising it may reach a few thousands. [79] The calculations of such configurations require invoking of the TB approaches, whereas band electronic structures of bilayers with reasonably small cells were obtained within DFT. [76,80], [81] Both types of computational approaches gave qualitatively similar results indicating that for the twist angles above 108 up to the symmetric point of 308, the dispersion in a twisted bilayer is linear as in single-layer graphene at the K point.…”
Section: Stacked Graphene Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…[77] As the twist angle decreases, the size of the unit cell enlarges [78] and the number of atoms comprising it may reach a few thousands. [79] The calculations of such configurations require invoking of the TB approaches, whereas band electronic structures of bilayers with reasonably small cells were obtained within DFT. [76,80], [81] Both types of computational approaches gave qualitatively similar results indicating that for the twist angles above 108 up to the symmetric point of 308, the dispersion in a twisted bilayer is linear as in single-layer graphene at the K point.…”
Section: Stacked Graphene Layersmentioning
confidence: 99%
“…[80] At an angle of less than 58, the p bands are flattened that is strictly different from their behavior in the monolayer and AB stacked bilayer. [79,82] However, after the value of $1.58, the bands acquire a parabolic dispersion. [82] The critical twist angle of $108 causes the formation of the AA and AB stacking regions in a bilayer and electron wave senses this local inhomogeneity.…”
Section: Stacked Graphene Layersmentioning
confidence: 99%
“…From a theoretical perspective, twisted bilayer graphene (TBG) has been examined extensively using both continuum [6][7][8][9] and ab-initio [10][11][12][13][14] approaches. These studies have shown that the individual monolayers become significantly decoupled by the rotational faults.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic properties of moiré crystals depend sensitively on the ratio of the interlayer hybridization strength, which is independent of twist angle, to the band energy shifts produced by momentum space rotation (5)(6)(7)(8)(9)(10)(11)(12). In bilayer graphene, this ratio is small when twist angles exceed about 2° (10,13), allowing moiré crystal electronic structure to be easily understood using perturbation theory (5).…”
mentioning
confidence: 99%